Studies of alpha-radioactivity in the marine environment - Shannon, L V (Department of Physics, 2016)
This dissertation deals with the alpha-radioactivity in the marine environment around South Africa, and the published literature relating to alpha-emitting nuclides in sea water and in marine organisms is surveyed in Chapter 1. As a first step in the investigation, the total alpha-activity of some 400 samples of marine life was determined using the thick-source alpha-particle detection technique. The relative contributions of the thorium series nuclides and "excess" unsupported polonium-210 were determined by using the "thorium pairs" technique and by studying the variation of the total alpha count-rate with time. This is considered in Chapter 2. The 'second phase of the investigation was to investigate the alpha-spectrum of marine life. This was done for several plankton samples using a large capacity ion-chamber. As expected several disequilibria were found to exist and the findings are discussed in Chapter 3. Unsupported polonium-210 accounted for the major proportion of the total alpha-activity in several marine groups, while radium-226 and daughters accounted for most of the long-lived radioactivity. Thorium series elements were also present. Using the ion-chamber data together with total alpha-counting data, an estimate of the radium-226 content of plankton was made.